(untitled) (Edad Media. Revista de Historia, 2025)
This article analyses the strategic options and choices with which one of the smallest kingdoms in Western Europe faced its military commitments during the final centuries of the Middle Ages. Drawing on contemporary chronicles and administrative documentation, it examines how Navarre, faced with a situation of strong demographic imbalance with its neighbouring powers and potential enemies, most frequently resorted to active defence, not exempt from episodes of aggression, as the most strategic solution.